Strategy To Strengthen Micro Small Medium Enterprises In Jatiluwih Village Through Financial Management And Digitalised Marketing - Desak Ayu Sriary Bhegawati; I Made Perdana Skolastika; Ni Made Satya Utami (Help: Journal of Community Service, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Jatiluwih Village face challenges in financial management and product marketing, largely due to their reliance on traditional methods. These businesses lack structured accounting systems and primarily use limited marketing channels, such as word-of-mouth and local exhibitions. This study aims to address these challenges by enhancing financial management practices and introducing digital marketing strategies to MSMEs in Jatiluwih Village. Training sessions were conducted, focusing on essential bookkeeping skills and the utilization of digital platforms for marketing. The primary participants were MSME owners, with special emphasis on women entrepreneurs, leveraging the expertise of PMM Unmas students in finance and marketing. The findings indicate that adopting structured financial management and digital marketing can significantly improve operational efficiency and expand market reach for MSMEs. These improvements are expected to contribute to the sustainable growth and long-term success of the enterprises in the digital era.